Superação de dormência e influência da temperatura, substrato e fotoperíodo na germinação de sementes de Erythrina crista-galli L. (FABACEAE) - Mello, Luciano Moura de (2011)
- Erythrina crista-galli L. (FABACEAE), known in Rio Grande do Sul as Corticeirado-banhado, the tree is a native of Brazil, Uruguay, Paraguay, eastern Bolivia and Argentina. It is found in swampy or marshy meadows, very common in the forest formations of galleries and is grown for ornamental purposes and restore natural environments, since it is well adapted to relatively dry and humid environments and natural formations composed of wide area distribution. The Rules for Seed Analysis - RAS (2009) have no guidelines for testing of germination of the species. The objective of this study was to evaluate the performance of three treatments to overcome seed dormancy (sulfuric acid, hot water and mechanical scarification) and conditions for the germination tests: two substrates suitable for the size of the seeds of E. crista-galli (sand and between paper, as stated in the RAS 2009), and photoperiod of 8 and 16 hours of light, subjected to temperatures of 15, 20, 25, 30 and 35°C and still perform biometric evaluations in fruits and seeds. Seeds from fruits collected from seven adult dies in a fragment of gallery forest near the Dam's Emergency Piraizinho in Bagé, RS (Coord. 31º 17' 30.55''S - 54º 10' 22.55''W) in January 2011. Tests were conducted at the Laboratory of Seed Analysis (LAS) Institute of Plant Breeding Biotechnology (INTEC), University of the Campaign, in Bagé, Brazil. Due to the limited availability of viable seeds (46% of the total collected), we used four replicates of 10 seeds in each treatment. The best performance on tests of dormancy breaking was the mechanical scarification with sandpaper nº 80, the end opposite the micropyle (no soaking) and sterilized and later with 5 min exposure to sodium hypochlorite 1%. Was initially carried out a test to determine best substrate and photoperiod, the experiment carried out at a temperature of 20-30ºC. The test results showed no difference (Tukey, 5%) between any of the treatments for both substrates tested for photoperiods. However, in order to simplify the routine laboratory work on standardized tests after using the substrate between paper and a photoperiod of 8 hours of light. Of evaluation results showed that the optimum temperature for germination tests of E. crista-galli (scarified mechanically with sterile with sodium hypochlorite 1% for 5 minutes, the substrate between paper and 8h of light) was the constant temperature of 30º C (temperature of better performance of abortion), even if not presented with a difference for the alternating temperature of 20-30º C. The germination speed index (GSI) of the seeds also performed best at 30° C, with an average of 46%. This result, however, no difference of the average verified at constant temperatures of 20, 25 and alternating 20-30° C. The evaluation of the average time of germination showed that the temperature alternating 20-30° C germination showed the best result, with 8 days, followed by the temperature of 30, 25 and 20° C, with no differences of the first and varying these, between 8 and 9 days.